2020
DOI: 10.1155/2020/8019360
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Hypertension as a Risk Comorbidity Associated with COVID-19 Pathology

Abstract: Coronavirus disease 2019 (COVID-19), caused by the novel coronavirus severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2), is an ongoing global public health challenge. Current clinical data suggest that, in COVID-19 patients, arterial hypertension (AH) is one of the most common cardiovascular comorbidities; it can worsen outcomes and increase the risk of admission to intensive care unit (ICU). The exact mechanisms through which AH contributes to the poor prognosis in COVID-19 are not yet clear. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 53 publications
(76 reference statements)
0
26
0
11
Order By: Relevance
“…Las estadísticas actuales en la COVID-19 refieren que la hipertensión arterial es una de las comorbilidades más comunes en los pacientes. Kamyshnyi et al, (2020) argumenta que el hecho de padecer esta enfermedad puede empeorar la evolución y aumentar el riesgo de progresión e ingreso en la unidad de cuidados intensivos. Se han estudiado los mecanismos por los cuales la HTA contribuye al mal pronóstico de la COVID-19, y aún no están claros.…”
Section: Discussionunclassified
“…Las estadísticas actuales en la COVID-19 refieren que la hipertensión arterial es una de las comorbilidades más comunes en los pacientes. Kamyshnyi et al, (2020) argumenta que el hecho de padecer esta enfermedad puede empeorar la evolución y aumentar el riesgo de progresión e ingreso en la unidad de cuidados intensivos. Se han estudiado los mecanismos por los cuales la HTA contribuye al mal pronóstico de la COVID-19, y aún no están claros.…”
Section: Discussionunclassified
“…Our study shows that the percentage of good outcomes in hypertension decreases 50% and the risk of adverse outcomes increases more than 3 times. COVID-19 patients with hypertension should be given additional attention to prevent worsening of their clinical outcomes (4,18). Instruction of blood pressure control in hypertensive patients is very important for clinical treatment of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that patients with older age and chronic underlying conditions might have a high risk of experiencing intensive care and death. Moreover, current clinical data suggest that, in COVID-19 patients, hypertension can worsen outcomes and increase the risk of admission to intensive care unit (ICU) (4). Previous clinical trials showed that SARSCoV-2 enters cells through angiotensinconverting enzyme 2(ACE2) receptors (5); high blood pressure is likely to increase COVID-19 mortality by affecting lung function and impairing oxygen delivery(6).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of death in covid patients with hypertension is 3,36 times higher. Based on the analysis derived from a backward stepwise logistic regression analysis it was obtained: male; age ≥60 years; smoking history; hypertension; lymphocyte≤ 0.8 * 109/L; PO2/FiO2≤ 260; logistic regression analysis: male; age ≥60 years; smoking history; hypertension; lymphocyte≤ 0.8 * 109/L; PO2/FiO2≤ 260; IL-6 ≥ 13pg/ml; IL-2R ≥ 1000pg/ml; positive sputum or sanguine culture for bacteria; fungi infection; multilobular infiltration [31,32]. Pneumonia is reported to be the most frequent cause of death in Covid 19 disease both for adults and children [33].…”
Section: Discussionmentioning
confidence: 99%